Sensibilização ambiental em espaços educativos usando o tema da poluição híbrida na lagoa do Parque São Pedro na cidade de Manaus/AM - Machado, Ailton Cavalcante (2021)
Water is an essential natural resource for the survival of living beings in their diversity of species, ecological systems, and the planet itself. Although its importance is vital, human pollution of water resources has had negative effects on the environment, even causing water scarcity in some places. Now, one of the alternatives to change this situation is to make people aware of environmental issues about taking care of this resource. For these reasons, considering these times of the pandemic, this research aims to understand how environmental awareness occurs in relation to the theme of water pollution, according to environmental values, using the lake at São Pedro Park, Manaus /AM, as place of research. With the participation Fifth graders attending the Professor Nilton Lins Municipal School. This is a study based on a qualitative approach, with the support of bibliographic research, textbook analysis and didactic sequence from the perspective of distance teaching, in addition to research techniques, such as the application of forms, using Google Forms platform, semi-structured interviews, children's drawing, and audiovisual recordings, we also used the WhatsApp messaging app. The study subjects were 20 students and 02 teachers who work at the abovementioned school. Interpretation and discussion of our results are based on the Qualitative Analysis by Minayo (2016) and Content Analysis by Bardin (2016), where the main results of the research points that technology can be a great ally in the Science teaching. Since technology constituted, in this research, the communication mechanism in which the students showed their learning regarding the problems of the studied lake and other hydric bodies in the region, such as rivers and streams. In this sense, we believe that pedagogical practices, long defended by the progressive aspect of Science education, can be adapted to any context, including the pandemic in which we currently live, highlighting the practical activities of research and manipulation of materials in scientific experiments carried out at home. Through these practices, it is possible to provide students with an education focused on thinking and doing scientific work, with an emphasis on the awareness process. From the Didactic Sequence, carried out through distance teaching, and considering the students’ writings and drawings, we can see that awareness indicators were built in those students. Keywords: Environmental Awareness. Educational Spaces. Water Pollution. Lake of São Pedro Park. Elementary School.